Motor Nerve Conduction Block Predicting Outcome of Guillain-Barre Syndrome - Niu, Jingwen; Liu, Mingsheng; Sun, Qing; Li, Yi; Wu, Shuang; Ding, Qingyun; Guan, Yuzhou; Cui, Liying (Frontiers in Neurology, 2018)
Introduction: Motor nerve conduction blocks (CBs) could be detected in both acute inflammatory demyelinating polyradiculoneuropathy (AIDP) and acute motor axonal neuropathy (AMAN). We aimed to identify the correlation between CBs and functional outcome in the two subtypes of GBS. Methods: Motor nerve conduction studies were performed in 17 patients with AIDP and 23 with AMAN. All patients were treated with intravenous immunoglobulin, and their disabilities were evaluated with Hughes functional grading scale before treatment, 1 month and 6 months after onset. Results: AMAN with CBs had higher reduction of Hughes grade (indicating more improved outcomes) at one month (1.71±0.83 vs 1±0.67, p=0.034) than AIDP with CBs. AMAN with CBs had higher reduction of Hughes grade at one month (1.71±0.83 vs 0.56±0.73, p=0.002) than AMAN without CBs. The reduction of Hughes grade at one month showed no significant difference between AIDP with and without CBs. Discussion: Motor nerve CBs in AMAN indicated better prognosis than in AIDP.